Assessing urban dynamics in Johannesburg’s public space : highlighting urban segregation and connectivity patterns of public space from an urban psychology perspective - Devenish, Paul (University of Pretoria, 2024)
Mini Dissertation (MArch(Prof))--University of Pretoria, 2024.